A pilot intervention to improve uptake and equality of childhood influenza vaccination in an area of Wales, through the introduction of a mixed delivery model including nursery school immunisation sessions - Ashley Akbari (Vaccine, 2023)
The schools-based influenza vaccination programme has seen consistently high uptake in Wales, however coverage in pre-school two and three-year olds is lower. One health board area (Cwm Taf University Health Board (UHB)) developed an intervention to offer live attenuated influenza vaccine (LAIV) for three-year olds attending nursery schools alongside the existing general practice (GP) programme. During the pilot, sessions were delivered by health visitors, working with school nurses. The mixed delivery model led to vaccination data being recorded in two separate data systems. To evaluate the impact of the pilot on overall vaccine uptake, data linkage was carried out within the Secure Anonymised Information Linkage (SAIL) Databank. Overall influenza vaccine uptake was calculated for each health board in Wales for two and three-year olds for the 2015–16, 2016–17, and 2017–18 influenza programmes. Uptake in two-year olds in Cwm Taf UHB and also uptake in three-year olds in other health boards in Wales were the comparison groups. Uptake of influenza vaccine in the 2015–16 (pre-intervention) period was 41.0% for three-year olds in Cwm Taf UHB. Following the intervention, coverage increased to 70.7% and 71.5% for 2016–17 and 2017–18 respectively. The same increases in uptake were not seen in two-year olds in Cwm Taf UHB or in three-year olds in non-intervention health boards. In Cwm Taf UHB resident three-year olds in 2015–16 there was an inequality gap in the uptake of 17.4 percentage points between the most and least deprived areas. Uptake increased across all deprivation quintiles in 2016–17 and 2017–18; and the inequality gap decreased to 10.3 and 13.4 percentage points respectively. Influenza vaccination uptake and equality of uptake in three-year olds can be improved by adopting a mixed delivery model across nursery school based immunisation sessions with the additional option of influenza vaccination at GPs.